Self‐care and Subjectivity among Mexican Diabetes Patients in the United States. (19th June 2014) - Seligman, Rebecca; Mendenhall, Emily; Valdovinos, Maria D.; Fernandez, Alicia; Jacobs, Elizabeth A.
Abstract : Type 2 diabetes is considered a public health crisis, particularly among people of Mexican descent in the United States. Clinical approaches to diabetes management increasingly emphasize self‐care, which places responsibility for illness on individuals and mandates self‐regulation. Using narrative and free‐list data from a two‐phase study of low‐income first‐ and second‐generation Mexican immigrants living with diabetes, we present evidence that self‐care among our participants involves emotion regulation as well as maintenance of and care for family. These findings suggest, in turn, that the ideology of selfhood on which these practices are based does not correspond with the ideology of selfhood cultivated in the U.S. clinical sphere. Divergence between these ideologies may lead to self‐conflict for patients and the experience of moral blame. We argue that our participants use their explanations of diabetes causality and control as a form of self‐making, which both resists such blame and asserts an alternative form of selfhood that may align more closely with the values held by our Mexican‐American participants.